The paradox struggle between the Islamic and conventional banking systems - Muneeza, Aishath; Wisham, Ismail; Hassan, Rusni (JAPSS Press, 2010)
Malaysia is a multi religious and a multi ethnic society with a plural legal structure. The banking system of country is essentially dual in nature and hence, there are two different sets of legal framework working simultaneously. Today, the Islamic Banking system which emerged in 1983 has levelled up to the conventional banking system which had rooted itself in the society a long time ago. Whether we believe it or not there are challenges and clashes at hand due to the existence of the dual system in the society and they need to be addressed properly, so that the clashes between these two types of banking system can be minimized. There are several quarrels between conventional and Islamic Banking laws. Some of these clashes are created due to the application of common law or conventional law based legislation to resolve the problems in the Islamic banking system. The impact of this is huge, primarily because, Islamic economics has a different premise from conventional banking and applying the same legal principles to resolve disputes for both markets does not work. Unlike conventional banking’s capitalist conviction that winner takes all, Islam argues for a fair distribution of profit and loss and bans purely speculative activity.